(The Effects of Storage Time on The Yield of Garlic Oil) - H Guring Pohan (Balai Besar Industri Agro, 1989)
Garlic, obtained from Central Java, was distilled using cohobation method.The distillate was collected within 2.5 hrs. after first drop of oil produced. The treatment given was the storage of minced garlic at room temperature for 0,1,2,3 and 4 days before distillation. The highest yield, 0.122%, was obtained from garlic of 1 day storage. The refractive index of the oil ranged from 1.5701 to 1.5795, while the specific gravity was 1.0907 - 1.1123.